Photoactive WS2 nanosheets bearing plasmonic nanoparticles for visible light-driven reduction of nitrophenol. Issue 36 (14th April 2016) - Lee, Hye-Rim; Park, Jung Hyun; Raza, Faizan; Yim, DaBin; Jeon, Su-Ji; Kim, Hye-In; Bong, Ki Wan; Kim, Jong-Ho
Abstract : Photoactive WS2 nanosheets bearing silver nanoparticles as novel photocatalysts for the reduction of 4-nitrophenol. Abstract : Semiconducting WS2 nanohybrids with different sizes of silver nanoparticles are designed via amine-assisted in situ reduction and growth of Ag + ions. These nanohybrids exhibit characteristic photocatalytic activity for the reduction of 4-nitrophenol as a function of their structure.